Pendidikan dan Latihan Kesehatan Gigi dan Mulut serta Kaitannya dengan Penyakit Sistemik pada Lansia di Panti Werdha Wisma Mulia - Christin Maitimu, Fergy; Aryani Hayuningtias, Ria; Ihsan Rizal, Muhammad; Anggara Putranto, Ricky; Astuti, Luki (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
The increasing number of elderly individuals in Indonesia, accompanied by rising health issues, particularly concerning oral health and its association with systemic conditions, is a notable concern. Community service activities in the form of education and training on oral health and its connection to systemic diseases among the elderly at Panti Werdha Wisma Mulia are expected to enhance awareness of the relationship between oral health and systemic conditions among the elderly and foster habits of maintaining oral health. There were 29 participants who were residents of Panti Werdha Wisma Mulia involved. Based on the pre-test and post-test results, there was an observable increase in knowledge among the participants regarding oral health, systemic diseases, and their interrelation. Furthermore, it is hoped that healthy lifestyle patterns, especially those related to oral health, will be established as they are closely linked to the systemic conditions of the participants.